Contextualized 7Taps Microlearning Modules for Enhancing Metacognitive Skills of Grade 11 Students - Gabelo, Raymundo Jr. R. (International Journal on Integrated Education, 2025)
In recent years, educational institutions had increasingly adopted various technological tools to facilitate learning, improve engagement, and promote self-directed learning. This study contributed valuable insights into how the Grade 11 students' metacognitive skills can be enhanced to improve their educational outcomes. Specifically, utilizing contextualized 7taps Microlearning Modules in Practical Research 1 subject. This quantitative quasi- experimental study focused primarily on investigating the utilization of contextualized 7taps microlearning modules to enhance the metacognitive skills of grade 11 students at Bigaa Integrated National High School. The participants were 30 learners from 11- TVL, specifically 15 students from the HE strand and 15 students from the ICT strand. These learners utilized the tablets provided by the school and the local government of Cabuyao City. Both the control and experimental groups initially showed "Unsatisfactory" performance in Practical Research 1, highlighting the need for instructional support. After the intervention, both groups improved to a "Satisfactory" level, with the experimental group (using 7Taps) performing slightly better. However, the difference between the two groups was not statistically significant. Despite this, the study confirmed that both traditional and microlearning methods effectively improved research skills. The 7Taps platform offered a self-paced, engaging way for students to reflect and build metacognitive strategies. The study emphasized the role of digital tools in enhancing critical thinking, problem-solving, and research literacy. It concluded with a call for further research on the long-term impact of microlearning, the most effective digital tools, and the necessary teacher training to fully leverage technology in research instruction.